Deradicalization of Islamic Teaching at Public Senior High School in Pariaman City, West Sumatra - Bulanov, Akdila (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2022)
The phenomenon of violence in the name of Islam gains various responses by which Muslims are often spacegoated. Jihad value which is thought in Islam is often used as an alibi to justify violence. An education system such as high school is the perfect place to teach religious radicalism. It is like two sides of a coin; on the one hand, the instruction can help religious teachers instill Islamic teachings, but on the other hand, it tends to provoke students to become intolerant. The focus of this research was the teachers and students of Public Senior High School Number 1 of Pariaman City, West Sumatra. Qualitative method was used in conducting this study. It aimed at finding deradicalization activities of Islamic religious learning at Senior High School Number 1 of Pariaman City. The result of the study shows that high school students are the perfect objects to accept the doctrine of radicalization. Hence, high school students are often targeted as terrorist recruitment targets. The government through schools has the capability to make tools to identify radical ideas taught to the students, one of which was carried out at Senior High School Number 1 of Pariaman City through deradicalization of Islamic teaching.